Bridging Theory and Risk Reality: Gap Analysis of Disaster Mitigation Competencies in Indonesian Civil Engineering Education Curriculum - Budiana, Ida Bagus Putra; Kurniadi, Anwar; Prihantoro, Mitro; Setiawibawa, Rachmat (International Journal of Education, Vocational and Social Science, 2026)
Amidst the increasing intensity of natural disasters in Indonesia, the role of civil engineers has evolved from merely designing physical structures to becoming crucial agents in disaster resilience. However, there is a clear discrepancy between the technical-static nature of civil engineering higher education curricula and the dynamic and multidisciplinary needs of disaster mitigation in the field. This study aims to diagnose this competency gap through a Systematic Literature Review (SLR) method using the PRISMA 2020 protocol. Data were collected from the Dimensions, Scopus, and Web of Science databases, resulting in 10 selected articles that were analyzed thematically. The results revealed that the main gap lies not in structural calculation abilities (hard engineering), but in deficits in “soft” competencies such as risk communication, policy advocacy, and post-disaster management. This study also identified that conventional (didactic) teaching methods are ineffective and recommended the adoption of new pedagogical strategies such as Forensic Engineering and humanitarian project-based learning. This research offers a curriculum mapping framework as a strategic solution to integrate disaster management competencies without overburdening the existing curriculum, in order to produce civil engineers who are resilient and responsive to risks.